2008
DOI: 10.1037/1931-3918.2.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Group supervision practices at psychology predoctoral internship programs: 15 years later.

Abstract: This national survey was conducted to answer several questions including: how predoctoral training sites practice group supervision, how these results compared to a similar survey sent in 1991 (Riva & Cornish, 1995), and whether group process and multicultural considerations are incorporated into group supervision practices. The original survey included 157 group supervisors from sites listed in the 1991-1992 APPIC Directory, while the current study's respondents included 162 group supervisors from sites in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 16 publications
2
38
0
1
Order By: Relevance
“…Such information and insights can be instrumental in supervisees' development and are, in some respects, unavailable in individual supervision. These new forms of learning are also among the themes of group supervision discussed by Linton (2003) and those identified by Riva and Cornish (2008) in their study of doctoral interns who received group supervision. The participants also emphasized the important normalization or validation of experiences and feelings that occurred for supervisees.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such information and insights can be instrumental in supervisees' development and are, in some respects, unavailable in individual supervision. These new forms of learning are also among the themes of group supervision discussed by Linton (2003) and those identified by Riva and Cornish (2008) in their study of doctoral interns who received group supervision. The participants also emphasized the important normalization or validation of experiences and feelings that occurred for supervisees.…”
Section: Discussionmentioning
confidence: 94%
“…The American Association for Marriage and Family Therapy (AAMFT, 2007) defines individual supervision as ''face-to-face contact between one supervisor and a maximum of two MFTs=trainees' ' (p. 17). Riva and Cornish (2008) found that 8% of psychology training programs conducted group supervision in their predoctoral internships with just two participants in the group. Also, in reviewing clinical supervision formats that are commonly used in the United Kingdom, Milne and Oliver (2000, p. 294) referred to ''individual supervision in a group,'' whereby one supervisor provides ''one to one supervision on a rotational basis within a group (e.g., 45 minutes with each of two supervisees).''…”
Section: A Qualitative Examination Of Supervisors' Experiences Of Thementioning
confidence: 98%
“…Yalom and Leszcz (2005) recognized the importance of the supervision of groups in the development of effective group leaders. Yet, it has also been observed that despite the small but growing empirical literature on Goodrich and Luke/LGBTQ GROUP SUPERVISION 23 group supervision (Linton & Hedstrom, 2006;Riva & Cornish, 2008), little has been written about the best practice processes, interventions, or applications within the supervision of group leaders (DeLucia-Waack & Riva, 2010). Increasingly, group supervision models have been developed to provide a cognitive template to organize and structure the interventions of group leaders and supervisors (Luke & Bernard, 2006;Okech & Rubel, 2007;Rubel & Okech, 2006).…”
mentioning
confidence: 96%
“…In a recent nation-wide survey (USA), Riva and Cornish (2008) assessed how predoctoral training sites in clinical and counselling psychology practice group supervision with regard to format, frequency, and structure. A total of 167 supervisors, more than half with substantial experience with group supervision, responded to an anonymous electronic questionnaire.…”
mentioning
confidence: 99%